2021
DOI: 10.48550/arxiv.2108.11391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cepheid Metallicity in the Leavitt Law (C-MetaLL) survey: I. HARPS-N@TNG spectroscopy of 47 Classical Cepheid and 1 BL Her variables

V. Ripepi,
G. Catanzaro,
R. Molinaro
et al.

Abstract: Classical Cepheids (DCEPs) are the most important primary indicators of the extragalactic distance scale. Establishing the dependence on metallicity of their period-luminosity and period-Wesenheit (𝑃𝐿𝑍/π‘ƒπ‘Š 𝑍) relations has deep consequences on the calibration of secondary distance indicators that lead to the final estimate of the Hubble constant (H 0 ). We collected high-resolution spectroscopy for 47 DCEPs plus 1 BL Her variables with HARPS-N@TNG and derived accurate atmospheric parameters, radial veloci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…R21 derived βˆ’0.20 Β± 0.13 from 66 Cepheids with HST photometry Ripepi et al (2021). used a larger ground-based sample of N = 317 fundamental and first-overtone pulsators to derive βˆ’0.37 Β± 0.09 on the ground system with similar filters, steeper by ∼ 1.5 Οƒ than R21 but less applicable here due to the presence of overtones and objects with low accuracy Groenewegen (2018).…”
mentioning
confidence: 99%
“…R21 derived βˆ’0.20 Β± 0.13 from 66 Cepheids with HST photometry Ripepi et al (2021). used a larger ground-based sample of N = 317 fundamental and first-overtone pulsators to derive βˆ’0.37 Β± 0.09 on the ground system with similar filters, steeper by ∼ 1.5 Οƒ than R21 but less applicable here due to the presence of overtones and objects with low accuracy Groenewegen (2018).…”
mentioning
confidence: 99%
“…However, we should note that based on their sample size, Β±15 Β΅as was the maximum possible precision, which would be insufficient to determine an offset on the small scales of the aforementioned studies. Ripepi et al (2021) found a +15 Β± 15 Β΅as offset by comparing 7 of the Cepheids with HST scanning parallaxes from Riess et al (2018) to the EDR3 parallaxes, though they emphasize that this is a small sample where two of the stars have large scatter with respect to the rest of the sample. Their overall result indicates the L21b offsets sufficiently correct the parallaxes within the quoted uncertainties.…”
Section: Parallax Offsetmentioning
confidence: 93%
“…Kennicutt et al 1998;Freedman et al 2001;Sakai et al 2004;Storm et al 2004;Macri et al 2006;Scowcroft et al 2009;Riess et al 2016;Breuval et al 2021). However, many of these studies have error bars which are nearly as large as the quoted magnitude of the metallicity effect itself, and even very recent determinations based on Gaia EDR3 data have disagreed by a factor of two (Breuval et al 2021;Ripepi et al 2021). Further, some studies (e.g.…”
Section: Metallicitymentioning
confidence: 99%
See 1 more Smart Citation